ChemInform Abstract: Tetrasubstituted Pyrazinones Derived from the Reaction of Praziquantel with N‐Bromosuccinimide. Issue 2 (January 2015) - Zhao, Qingjie; Wang, Chunkai; Ezell, Edward L.; Dong, Yuxiang; Vennerstrom, Jonathan L.
Abstract The cytotoxicity of the synthesized pyrazones are tested against several protozoan parasites.